2009
DOI: 10.1194/jlr.m800361-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic inhibition of atherogenesis in apoE−/− mice between pravastatin and the sPLA2 inhibitor varespladib (A-002)

Abstract: Secretory phospholipase A2 (sPLA 2 ) activity promotes foam cell formation, increases proinflammatory bioactive lipid levels, decreases HDL levels, increases atherosclerosis in transgenic mice, and is an independent marker of cardiovascular disease. The effects of the sPLA 2 inhibitor A-002 (varespladib) and pravastatin as monotherapies and in combination on atherosclerosis, lipids, and paraoxonase (PON) activity in apoE 2/2 mice were investigated. Male apoE 2/2 mice were placed on a 12-week high-fat diet supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…91 In a guinea pig model in which sPLA 2 -IIA and other isoforms are expressed, treatment with varespladib did not change plasma cholesterol levels but reduced aortic lipid accumulation. 90 The fact that varespladib exerts an antiatherogenic effect in C57BL/6 apoE Ϫ/Ϫ mice that do not express sPLA 2 -IIA suggests that sPLA 2 -V, sPLA 2 -X, or both contribute to atherosclerosis and are targeted in vivo by this inhibitor.…”
Section: Spla 2 Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…91 In a guinea pig model in which sPLA 2 -IIA and other isoforms are expressed, treatment with varespladib did not change plasma cholesterol levels but reduced aortic lipid accumulation. 90 The fact that varespladib exerts an antiatherogenic effect in C57BL/6 apoE Ϫ/Ϫ mice that do not express sPLA 2 -IIA suggests that sPLA 2 -V, sPLA 2 -X, or both contribute to atherosclerosis and are targeted in vivo by this inhibitor.…”
Section: Spla 2 Inhibitionmentioning
confidence: 99%
“…Varespladib has been shown to significantly reduce atherosclerosis by 40% to 75% in apoE Ϫ/Ϫ mice fed a high-fat diet 89,90 and to attenuate the development of angiotensin II-induced aortic aneurysms. 89 However, in 1 of the 2 studies in apoE Ϫ/Ϫ mice, 89 plasma total cholesterol was also decreased, which may contribute to the atheroprotective effect of varespladib.…”
Section: Spla 2 Inhibitionmentioning
confidence: 99%
“…5 Varespladib methyl is a nonspecific pan-sPLA 2 inhibitor with favorable effects on atherosclerotic lesions in animal studies. 11 Initial studies demonstrated that varespladib reduced levels of sPLA 2 -IIA by more than 90%, in addition to lowering low-density lipoprotein cholesterol (LDL-C) and Creactive protein (CRP) in patients with stable coronary disease and ACS. [12][13][14] The Vascular Inflammation Suppression to Treat Acute Coronary Syndrome for 16 Weeks (VISTA-16) study was designed to evaluate the effects of varespladib on cardiovascular risk in patients with ACS.…”
mentioning
confidence: 99%
“…Several studies in mice and humans have linked NURR1 and secretory phospholipase A2, the ligand of PLA2R1, to lipoprotein metabolism, lipolysis, foam cell formation, and development of atherosclerosis. [25][26][27][28] We investigated liver expression of both genes and performed expression QTL mapping in F2 mice to test whether we could detect significant differences in transcript levels based on allele status. Both genes were expressed in liver, but we did not detect significant expression differences or expression QTLs in F2 mice (Supplemental Figure III).…”
Section: Potential Candidate Genes At Chrmentioning
confidence: 99%